PEMBIASAAN SIKAP BIJAK DALAM MENGELOLA UANG PADA ANAK PAUD DI DESA BENTO KABUPATEN KERINCI - Wantia, Natasya; Rahmadani, Mirna; Sefdina, Lesa Dara; Tiara, Tiara; Desiana, Desiana (RANGGUK: Jurnal Pengabdian Kepada Masyarakat, 2023)
Character-building education is a long process that must begin from the time of the birth of children, even though the impact is only felt after the children grow up. Instilling a wise attitude to manage money through saving habits will be one of the pillars that will support a child's life later, when he grows up. This activity aims to introduce how to manage money to PAUD students in Bento village, Kerinci District. This activity was carried out in June 2022 through several stages, namely: 1) introducing ECCE students to saving; and 2) distributing piggy banks to students and inviting them to set aside spending money periodically. The results of the activity showed that student savings in one month ranged from Rp 2,000 to Rp 70,000. This saving activity needs to be done sustainably, so a wise attitude toward managing money is expected to be one of the characteristics of students.